Trends in Interactive Learning Media for Science Education in Secondary Schools: A Systematic Literature Review - Nur Azmi Afifah Diens; Khaerudin Khaerudin; Cecep Kustandi; Imam Fitri Rahmadi (FKIP - Universitas Riau, 2026)
Science education at the secondary level increasingly demands interactive, technology-driven approaches to enhance learning quality. This study aims to identify global trends in the use of interactive learning media in secondary school science education from 2020 to 2024. A Systematic Literature Review (SLR) method following the PRISMA 2020 framework was employed, analyzing 29 peer-reviewed articles selected from the Scopus database using strict inclusion criteria. The results show that web-based media and interactive e-books are the most commonly used types, followed by augmented reality, virtual reality, game-based learning, and simulations. Regarding learning outcomes, cognitive aspects such as conceptual understanding and academic achievement are most frequently reported, followed by critical thinking skills, learning motivation, affective attitudes, creativity, process skills, and scientific literacy. Overall, interactive learning media support not only cognitive development but also motivation and essential 21st-century skills. The findings underscore the importance of integrating interactive media to improve instructional effectiveness and foster comprehensive student competencies in secondary science education.